1997
DOI: 10.1123/pes.9.1.55
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Karate Training on Flexibility, Muscle Strength, and Balance in 8- to 13-Year-Old Boys

Abstract: The effect of 6 months of twice weekly karate training on flexibility, balance, and strength was evaluated in 14 boys who perform karate as beginners (age M = 10.3 ± 1.8) and a group of the same age who had never been involved in martial arts (n = 10; age M = 10.9 ± 1.4). All subjects were pretested and posttested on the following: flexibility of upper extremity (shoulder), hamstrings and quadriceps; strength, including handgrip strength and concentric flexion/extension of quadriceps; and balance, with eyes ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 0 publications
1
23
0
3
Order By: Relevance
“…30 High intensity intermittent training seems to have no influence on flexibility whereas other sports activities, e.g., karate, improved flexibility. 31,33 In the present study flexibility increased after training. Flexibility in our group was lower compared to healthy children of the same age but was in normal range (Fig.…”
Section: Training Effectssupporting
confidence: 61%
See 2 more Smart Citations
“…30 High intensity intermittent training seems to have no influence on flexibility whereas other sports activities, e.g., karate, improved flexibility. 31,33 In the present study flexibility increased after training. Flexibility in our group was lower compared to healthy children of the same age but was in normal range (Fig.…”
Section: Training Effectssupporting
confidence: 61%
“…The finding of increased strength, balance and aerobic exercise capacity are in line with previous studies in healthy children. [31][32][33]43 Only a few controlled studies are available on the effects on various aspects of physical fitness. Baquet et al 31,32 showed significant improvements of maximal aerobic performance, explosive strength and distance covered in a 7 min running test, but not flexibility.…”
Section: Training Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among young karatekas, training influences motor skills such as flexibility, muscle strength, and balance (Violan, Small, Zetaruk, & Micheli, 1997). Preadolescent karatekas showed a significant improvement in static body balance after high intensity karate training lasting one week (Vando et al, 2013).…”
mentioning
confidence: 98%
“…The effect of martial arts and combat sports practice (i.e., Judo, Taekwondo, Karate) was investigated in several studies among youth 3,4 , adolescents 5,6 , elders [7][8][9] and people suffering from some disorders (e.g., developmental coordination disorder, multiple sclerosis) 10,11 . Most of these studies reported that martial arts and combat sports training involved a significant improvement in physical and motor abilities.…”
Section: Introductionmentioning
confidence: 99%